Increasing Nurses’ Job Satisfaction with Nursing Rounds - Ernalinda Rosya; Elly Nurachmah; Deswita . (Faculty of Nursing, Universitas Andalas, 2018)
Background: The nursing staff as one of a member of the healthcare providers team that determine the quality and the image of the hospital should improve their healthcare services quality. Low job satisfaction can affect the condition of anorganization that manifested in the form of labour strikes, absence and job turnover. Nursing round was activity that expected to increase the job satisfaction of nurses. Job satisfaction of nurses will have an effect on patient satisfaction and the quality of hospital healthcare services. Purpose: To identify the effect of nursing rounds on nurses’ job satisfaction. Method: Pre-experimental research using the existing design without a comparison group, the sample size was 20 people. This study used a one group pre-test and post-test design without control. The Instrument in this study was questionnaire and observation sheet. Result: The results before the nursing round on nurses’ job satisfaction level of the nurses on all sub variables was low. After the implementation of nursing round, the level of job satisfaction of the low nurses was increasing in number of sub autonomy and interaction variables. The decrease in the number of implementing nurses whose level of job satisfaction is low occurs in the sub variables of professional status and task requirements. Conclusion: So showed a significant effect on the level of nursing rounds on job satisfaction of hospitalization nurses. The optimize job satisfaction nurses and nursing rounds with assembles relevant policies.